Makna Pola Asuh Kepala Kamar sebagai Role Model bagi Santri - Abd. Mughni; Iskandar (Fakultas Dakwah Universitas Ibrahimy, 2022)
Islamic boarding school as an educational institution is the right choice to realize the biggest go- al because pesantren is a place for students to gain knowledge, both religious and general knowledge. In the pesantren to make teaching and learning activities successful, a kiai is assisted by the head of the room. The purpose of this study was to describe the democratic parenting of the head of the ro- om for the students in the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo Situbondo. This research method uses qualitative research methods using a case study model. This study resulted in the meaning of democratic parenting as a role model for students, namely by providing education to students, providing religious examples, providing examples of good behavior, motivation, guidance, and showing the spirit of spiritualism in their students.